Dynamic Routing With Security Considerations (International Journal of Engineering and Computer Science, 2017)
This paper describes dynamic routing with securityusing a cryptographic algorithm which can be used in multiple organization system. The problem of security is the major issues for data communication over worldwide networks. The main objective of this paper is to propose a dynamic routing with security considered using strongest algorithm, such as Blow fish algorithm. Blow fish algorithm provides the strong security from the client to the server system. The dynamic routing avoids two consecutive packets on the same link and updates the routing information from neighbors of the router in the network.  The main aim of this  paper is a provide strong security from many organizations to a head of the organization, such as Banks, Colleges, Companies, Universities as they need a strong security for data communication. So this paper main issue is to provide strongest security and less time for data transmission from the clients to a server.